Rantai Nilai Pada Budidaya Kolam Ikan Air Tawar di Kota Bogor - Arief Nur Rakhman; Muhammad Firdaus; Rina Oktaviani (School of Business, Bogor Agricultural University (SB-IPB), 2017)
This study was conducted to determine the flow of the value chain of freshwater fish pond culture in the city. Research on the value chain actors freshwater fish farming in Bogor, mapping the value chain, the production cost and the Marginal value of the value chain. Actors involved in the value chain of freshwater fish farming pond in the city of Bogor is fish farmers, collectors and traders. From the analysis of the Margin, the mediator has the greatest Margin value.Keywords: fish culture, value chain, freshwater fish, value-chain analysis (VCA)Abstrak: Penelitian ini dilakukan untuk mengetahui alur rantai nilai budidaya kolam ikan air tawar di Kota. Anlisis penelitian yang digunakan adalah analisis rantai nilai/value-chain analysis (VCA). Hasil penelitian menunjukkan secara umum pada rantai nilai budi daya ikan ini yang mendapatkan margin terbesar ada pada aktor pengepul, dimana pengepul yang mempunyai akses dan informasi dua arah, baik itu informasi pasar ataupun informasi mencari petani ikan.Kata kunci: budi daya ikan, rantai nilai, ikan air tawar, value-chain analysis (VCA)